82.4k views
5 votes
A system of equations is shown below:n = 3m + 7n − 2m = 1What is the solution, in the form (m, n), to the system of equations? (3, 7)(1, 8)(−3, −2)(−6, −11)

1 Answer

4 votes

n = 3m + 7

n − 2m = 1

solve second equation for n

n - 2m = 1

n = 1 + 2m

now they are both equal to n, so

3m + 7 = 1 + 2m

solve for m

3m + 6 = 2m

6 = -1m

m = -6

plug in

n − 2(-6) = 1

n + 12 = 1

n = -11

check

-11 = 3(-6) + 7

-11 = -18 + 7

-11 = -11

m = -6

n = -11

D

User Nugs
by
6.1k points